1985
DOI: 10.1080/07315724.1985.10720075
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic changes during a marathon, with special reference to magnesium.

Abstract: In a single case study of a moderately trained, healthy man, physiologic changes during a marathon are reported. Blood was drawn prior to the race, at 1 hour and 2 hours into the race, at the end of the race, and after 1 hour of recovery. By 1 hour into the race, norepinephrine, epinephrine, and dopamine had increased nearly nine-fold, two-fold and five-fold, respectively. After 1 hour of recovery, epinephrine had returned to the pre-race value but norepinephrine and dopamine were still elevated. Cortisol incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…However, ionized and total extracellular Mg did not change in the same relation suggesting that part of the decrease in ionized Mg 2+ was evoked by binding of Mg 2+ to chelators in serum or towards cell membranes. Franz et al suggested that increased plasma free fatty acids during and after a marathon could be responsible for the observed decrease in Mg (Franz et al, 1985). However, this mechanism seems unlikely for the present short term exercise protocol.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, ionized and total extracellular Mg did not change in the same relation suggesting that part of the decrease in ionized Mg 2+ was evoked by binding of Mg 2+ to chelators in serum or towards cell membranes. Franz et al suggested that increased plasma free fatty acids during and after a marathon could be responsible for the observed decrease in Mg (Franz et al, 1985). However, this mechanism seems unlikely for the present short term exercise protocol.…”
Section: Discussionmentioning
confidence: 57%
“…However, other workers have reported both increasing and decreasing values for total [Mg] i after exercise (Casoni et al, 1990;Deuster et al, 1987;Lijnen et al, 1988). The reason for these controversial findings is not yet clear and might depend on different methodological approaches and/or exercise protocols (Franz et al, 1985;Rayssiguier et al, 1990).…”
Section: Discussionmentioning
confidence: 94%
“…This change could reflect a redistribution of serum magnesium into either muscle tissue, adipocytes, or red blood cells (McDonald and Keen, 1988). In a case study of a marathon runner during a race, Franz et al (1985) found that during the race serum magnesium increased followed by a decrease by the end of the race. Deuster et al (1987) reported that a high intensity anaerobic exercise produced a significant increase in urinary excretion of magnesium on the day of the exercise and then returned to normal.…”
Section: Magnesium Statusmentioning
confidence: 97%
“…Runners exhibited increased excretion of both catecholamines and CS; Mg supplements significantly decreased their CS ex cretion [9]. A marathon runner, whose CS levels gradually increased during a race, attained twice pre-race values at the end of the race [26]. A mixed CS with glucocorticosteroid (GCS) and mineralocorticosteroid (MCS) activity caused negative Mg balance in normal volunteers, mostly by interfering with intestinal Mg absorption [27].…”
Section: Corticosteroids During Stress; Interrelations With Magnesiummentioning
confidence: 99%